Adsorpsi dan Pelepasan Doxorubicin dari Permukaan Partikel Magnetit/Hidroksiapatit - Sri Murda Niati; Ahmad Fadli; Yelmida Aziz (Fakultas Teknik Universitas Riau, 2019)
Cancer is a disease caused by poor cell growth in body tissues. One effective method of dealing with cancer cell growth is the nanomedicine or nano drug delivery approach. Biocompatible, biodegredable and non-toxic drug delivery material for the body is magnetite / hydroxyapatite composite. This research uses hydrothermal method to produce magnetite / hydroxyapatite composites. Furthermore, to determine the performance of magnetite / hydroxyapatite composites as drug delivery through adsorption kinetics and mathematical models of doxorubicin decay on the surface of the composite and the value of the mass transfer coefficient. The concentration of doxorubicin used for adsorption was 520, 720, 920 (ppm) with a composite mass of 0.2 0.3 0.4 and 0.5 (grams) and an adsorption temperature of 30, 40, 50 (0C). The doxorubicin release model in the composite layer uses PBS solution media pH 7.4 with a temperature of 370C. The results obtained for doxorubicin adsorption kinetics on composite surfaces were 71.43; 55.56; 90.91 mg/g for temperature variations of 30, 40, 50 °C with (R2) is 0.980 and % SSE by 33% and kinetics constant adsorption 0.282. Decay of doxorubicin in vitro using PBS solution was obtained. The value of the mass transfer coefficient obtained increased with the increase in the mass of the magnetite/hydroxyapatite composite, for the mass of the magnetite/hydroxyapatite composite 0.2; 0.3; 0.4; and 0.5 grams (kc) values obtained were 1.1 x 10-4 g/cm2.minute, 4.4 x 10-4 g/cm2.minute, 9.9 x 10-4 g/cm2.minute and 2 , 1 x 10-3 g/cm2.minute.